Nagoya mathematical journal (Mathematical Institute, Faculty of Science, Nagoya University, 1950)
Issue for Mar. 1970 dedicated to Professor Katuzi Ono on his 60th birthday with portrait, sketch of his life, and list of mathematical papers.